MENINGKATKAN KECERDASAN INTERPERSONAL MELALUI PERMAINAN TRADISIONAL ANAK USIA 5-6 TAHUN DI TK TUNAS HARAPAN SEI LAMBU MAKMUR KECAMATAN TAPUNG KABUPATEN KAMPAR - Wartilah, Wartilah; Zulirfan, Zulirfan; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase intrapersonal intelligence in children ages 5 -6 years through traditional games in TK Tunas Harapan Makmur subdistrict Sei Lambu Tapung Kampar regency. This study is je nis studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 4-5 years are numbered 15 children in kindergarten Tunas Harapan Sei Lambu , The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The research shows that traditional games can improve intrapersonal intelligence in children aged 5-6 year. It can be seen from the increase in the average percentage of intrapersonal intelligence in the first cycle of 54.11%, which is in the category of less and an increase of 46.6% in the second cycle becomes 79.3% were located in both categories. Thus, traditional games can improve intrapersonal intelligence of children aged 5-6 years in kindergarten Tunas Harapan Makmur subdistrict Sei Lambu Tapung Kampar regency.Keywords : Intrapersonal intelligence, Traditional game